Tips and tricks in endocrine surgery - Ahmed, Shahzada K.; Scott-Coombes, David M.; Sharma, Neil; Stechman, Michael J.; Watkinson, John (Springer, 2014)
Endocrine surgery is a highly specialised field due to the technical nature of the procedures and associated risks. Despite this, endocrine operations sometimes fall to the general surgeon to deploy. Tips and Tricks in Endocrine Surgery aims to provide a concise summary of all aspects of endocrine surgery, taking into account the latest evidence and current expert opinion. The book comprises five sections covering the major endocrine organs and systems, each chapter focuses on one endocrine disorder and provides guidelines on the techniques, considerations and aspects of surgical care specific to each procedure. This book is an invaluable quick-reference resource that will appeal to higher surgical trainees in general surgery, endocrine surgery, ENT surgery and neurosurgery. Core surgical trainees preparing for examinations and consultants wishing to refresh their knowledge of the surgical management of endocrine disorders will also find this book useful.